Genders in the Life Course
XVIII, 329 p.
Keywords: This book treats the topic of gender and demographic behaviour during the life course in a comprehensive fashion. It covers a lot of ground, from the age at first intercourse over union formation and dissolution, fertility, migration, ageing, to excess male mortality, comparing genders behaviour and its determinants. It reports new findings of empirical research, mostly based on data from a number of European countries, making a good use of the Family and Fertility surveys and other international data base. This book is of particular interest to demographers, social scientists, academic scholars and private/ public-sector operators, particularly those who are interested in the roles of men and women, and the factors of possible asymmetries and disadvantages, with direct connections to the population policies.